A new companion to Homer - Morris, Ian, 1960-; Powell, Barry B. (Mnemosyne, Supplements, 1997)
This volume is the first English-language survey of Homeric studies to appear for more than a generation, and the first such work to attempt to cover all fields comprehensively. Thirty leading scholars from Europe and America provide short, authoritative overviews of the state of knowledge and current controversies in the many specialist divisions in Homeric studies. The chapters pay equal attention to literary, mythological, linguistic, historical, and archaeological topics, ranging from such long-established problems as the \'Homeric Question\' to newer issues like the relevance of narratology and computer-assisted quantification. The collection, the third publication in Brill's handbook series, The Classical Tradition , will be valuable at every level of study - from the general student of literature to the Homeric specialist seeking a general understanding of the latest developments across the whole range of Homeric scholarship.